2016
DOI: 10.1155/2016/2426413
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Reduces GFAP+ Cell Density in the Rat Hippocampus

Abstract: Anorexia nervosa is an eating disorder observed primarily in young women. The neurobiology of the disorder is unknown but recently magnetic resonance imaging showed a volume reduction of the hippocampus in anorexic patients. Dehydration-induced anorexia (DIA) is a murine model that mimics core features of this disorder, including severe weight loss due to voluntary reduction in food intake. The energy supply to the brain is mediated by astrocytes, but whether their density is compromised by anorexia is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
3
14
0
1
Order By: Relevance
“…Anorexia increased the number of reactive astrocytes in CA2 region and in the dentate gyrus more than two-fold. As indicated by the data presented in patients with anorexia nervosa, we observe a reduced density of GFAP + hippocampal cells and increased vimentin and nestin expression [13].…”
Section: Changes In the Density Of Gfap + Cells In An Animal Model Ofsupporting
confidence: 76%
See 1 more Smart Citation
“…Anorexia increased the number of reactive astrocytes in CA2 region and in the dentate gyrus more than two-fold. As indicated by the data presented in patients with anorexia nervosa, we observe a reduced density of GFAP + hippocampal cells and increased vimentin and nestin expression [13].…”
Section: Changes In the Density Of Gfap + Cells In An Animal Model Ofsupporting
confidence: 76%
“…Brak łaknienia zwiększał liczbę reaktywnych astrocytów w regionie CA2 oraz w zakręcie zębatym ponad dwukrotnie. Jak wskazują przedstawione dane u chorych z jadłowstrętem psychicznym mamy do czynienia ze zmniejszoną gęstością komórek GFAP+ hipokampa i zwiększoną ekspresją wimentyny oraz nestyny [13].…”
Section: Zmiany Gęstości Komórek Gfap+ W Zwierzęcym Modelu Jadłowstręunclassified
“…Other studies have reported neurohistological abnormalities in individuals with AN and in AN animal models indicating degeneration associated with "pseudoatrophia cerebri". A postmortem study showed quantitative and qualitative changes in neuronal dendritic spine morphology [37], and animal studies using dehydration-induced, forced food-restricted, or activity-based AN models have found reduced astrocytes in the hippocampus, corpus callosum, and cerebral cortex [9,[38][39][40]. Future studies need to collect biomarkers from cerebral spinal fluid to investigate possible degenerative processes caused by AN in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…The best-established animal model that mimics the core symptoms of AN, such as weight loss, hyperactivity, and amenorrhea, is the so-called activity-based anorexia (ABA) paradigm 22 , which combines restricted food availability with access to a running wheel. This combination results in starvation and voluntary hyperactivity in ABA animals; this seemingly contradictory activity can possibly be explained as food seeking behavior and is driven by lower leptin levels 22,23 . We established a modified version of the original ABA model by giving a limited amount of food instead of a limited time for feeding with the aim of preventing mortality in the animals 24,25 .…”
Section: Introductionmentioning
confidence: 99%